Comparison of the efficacy of LigaSure and laser for grade 2-3 hemorrhoids - Ali Kemal Taşkin; Bülent Özçetin (National Scientific Medical Center, 2023)
Aim: The aim of this study is to compare the efficacy of LigaSure and LH procedures in the treatment of grade 2-3 hemorrhoids. Material and methods: Demographic and clinical data of the patients were recorded retrospectively. A visual analogue scale (VAS) was used to evaluate the pain intensity of the patients after the procedure and a Likert-type scale was used to evaluate patient satisfaction surveys 6 months after the procedure. Results: Of the 66 patients, (mean age: 42.12±11.92 years, %72,7 male) 34 underwent LH procedure whereas 32 underwent LigaSure procedure. Spinal anesthesia was applied for 64 patients and general anesthesia was applied for 2 patients. Procedure time and time to return to work were significantly shorter in the LH group compared to the LigaSure group (900 vs. 1200 seconds, p<0.001, and 3.64±1.29 vs. 14.46±3.73 days, p<0.001). Late complications (abscess, relapse, pruritus, and seromucous discharge) were more common in the LH group, but the difference was not statistically significant (23.5% vs. 6.3%, p=0.08). VAS pain scores were significantly lower in the LH group (p<0.001). Although there was no significant difference between the treatment groups in terms of patient satisfaction, relapse was significantly less common in the LigaSure group (p=0.045). Conclusion: In patients with grade 2-3 hemorrhoids, LH may be preferred over LigaSure due to greater patient comfort, higher satisfaction rates, and fewer early complications. However, close follow-up of these patients is important due to the higher incidence of late complications with LH.